Fluctuation of serum vitamin E (α-tocopherol) concentrations during exacerbation and remission phases in patients with chronic fatigue syndrome - Miwa, Kunihisa; Fujita, Masatoshi (Heart and vessels, 2010)
The etiology of chronic fatigue syndrome remains unknown. Oxidative stress may be involved in its pathogenesis. Vitamin E is a major endogenous lipid-soluble antioxidative substance, and is consumed during the lipid peroxidation process. We studied a population comprising 27 patients with chronic fatigue syndrome (10 men and 17 women, 29 ± 6 years of age) and 27 age- and sex-matched control subjects. Serum vitamin E (α-tocopherol) concentrations were determined and expressed as mg/g total lipids (total cholesterol and triglyceride) to evaluate oxidative stress. Serum α-tocopherol concentrations (mg/g lipids) were significantly ( P < 0.001) lower in the patients with chronic fatigue syndrome (2.81 ± 0.73) than in the control subjects (3.88 ± 0.65). The patients with chronic fatigue syndrome were re-examined during a follow-up interval. After 8 ± 2 months, 16 patients exhibited a status that warranted re-examination during remission of the symptoms at a regular visit to our hospital (Group 1), while the remaining 11 did not (Group 2). The serum α-tocopherol levels were significantly elevated during remission as compared with those at baseline in Group 1 (2.71 ± 0.62 → 3.24 ± 0.83, P < 0.001). The levels did not significantly change after the interval in Group 2 (2.97 ± 0.86 → 2.85 ± 0.73, not significant). In conclusion, serum α-tocopherol concentrations were significantly lower in the patients with chronic fatigue syndrome as compared with the control subjects, suggesting increased oxidative stress in the former. The low level of serum α-tocopherol was ameliorated during the remission phase as compared with the exacerbation phase in the patients with chronic fatigue syndrome, suggesting that increased oxidative stress may be involved in the pathogenesis of chronic fatigue syndrome and might also be directly related to the severity of the symptoms of chronic fatigue syndrome.